Rethinking Impact Workshop: key issues - International Livestock Research Institute; CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation; CGIAR Institutional Learning and Change Initiative (2008)
Six key issues emerged from the Rethinking Impact Workshop (RIW): Understanding the complexity of poverty and change held in Cali, Colombia, March 26–28, 2008. The workshop discussed (1) how agricultural and natural-resources research can be more effective in contributing to solutions for poverty alleviation and improving gender, social inclusion and equity; (2) how its impact can be assessed; and (3) how such research and impact assessment can be brought into the mainstream.